Crawling Glazes on Mid-Century Modern Maritime Canadian Studio Pottery: Shared or Re-Created? - Owen, J. Victor; Adlakha, Erin; Carter, Delaney (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2023)
This paper presents compositional data for crawling glazes made by prominent studio potters in New Brunswick and Nova Scotia during the mid-20th century (Erica and Kjeld Deichmann, Eleanor and Foster Beveridge, and Carrie Mackenzie) with the objective of (1) identifying key glaze ingredients, and (2) determining whether glaze recipes were shared by these potters, or if the glaze produced by one (likely the Deichmanns) inspired others to re-create it. Crawling glazes are those that retract during firing, creating “islands”. They commonly have unusual compositions (e.g., high alumina contents) to ensure a high viscosity and surface tension, but crawling can also be triggered by treating the ceramic surface to minimize adhesion with the glaze prior to firing. The Deichmanns used different formulae to produce their signature “Snow on the Mountain” (SOTM) crawling glaze used on redware versus stoneware. Three of four of their analysed glazes are magnesian owing to the use of magnesium carbonate (the mineral magnesite); the fourth is highly potassic and calcic (suggesting the use of “pearl ash” and “whiting”) and less aluminous. The Beveridges’ counterpart, though visually-similar, has a distinct composition, and calcium-magnesium carbonate (dolomite) was used instead of magnesite. Crawling was ensured in most samples by high alumina contents. Mackenzie’s glaze is visually distinct (i.e., is brown, not white) and has very high lead and low alumina, lime and magnesia contents. Crawling in it and in the single low-alumina Deichmann glaze is attributed devolatilization of carbonate minerals, thick application and/or pre-glazing surface treatment. The analytical data suggest that the Deichmanns did not share specific details of their SOTM glaze formulae with the Beveridges, who evidently sought to re-create them. Mackenzie formulated a distinct crawling glaze, but also made knobbed wares likely inspired by the Deichmanns’ well-known “Kish” bowls.